Effect of Precipitates on Plastic Deformation Behavior of High Entropy Alloy Al0.3CoCrFeNi under High Strain Rate Loading - Das P.K.; Kumar V.; Khanikar P. (My University, 2025)
High entropy alloys (HEAs) are primarily known for their high strength and high thermal stability. These alloys have recently been studied for high strain rate applications as well. HEAs have been observed to exhibit different properties when subjected to different strain rates. Very few published results on HEAs are available for high strain rate loading conditions. In addition, modeling and simulation work of microstructural details, such as grain boundary and precipitates of HEAs have not yet been investigated. However, at an atomistic length scale, molecular dynamics simulation works of HEAs have already been published. In this study, a detailed microstructural analysis of plastic deformation of the material under high strain rate loading has been performed using dislocation density based crystal plasticity finite element modeling. The primary objective is, therefore, to assess the strengthening effects due to precipitates on a particular high entropy alloy Al0.3CoCrFeNi with ultrafine grains having randomly distributed NiAl precipitates. © 2021 American Society of Mechanical Engineers (ASME). All rights reserved.